Stabilitas Tanah Timbunan Sisi BH-1 Proyek Jalan Akses Pembangunan Jembatan Pulau Balang II - Juandra Hartono; Umi Khoiroh; Muhammad Saleh (Universitas Islam 45, 2022)
Problem on the road access landfill at Balang Island II Bridge is the landslide at STA 23+025 on left side slope (BH-1) caused by a swamp pond on the roadside. The landfill that cutted into the swampy area made the water get stuck on one side (water could not flow to the original condition). The research method is the form of direct observation in the field which focuses on the results of information and laboratory testing which is then processed and analyzed. The analysis obtained that the soil type on the spot is clay with N-SPT 6 – 29. There are 2 alternatives solutions for the problem. First, if there is a ROW problem, the treatments are watercourse, adding counterweight, wooden pile under the landfill and one layer Geotextile PP 50 (initial ground water level on exsisting condition with 90,4 kPa loads). Second, if there is no ROW problem, the treatments are watercourse, adding counterweight, wooden pile under the landfill and one layer Geotextile PET 100 (initial ground water level on top of landfill with 90,4 kPa loads). Based on technical analysis, the second solution was chosen because it has bigger safety factor, smallest settlement value, and shorter time implementation. However it is still need more detail technical justification to strengthen the desicion.